Perancangan Action Figure Lima Hero Hewan Khas Indonesia - Hadisiswanto, Bayu Dwi (Fakultas Sosial Humaniora dan Seni Usahid Surakarta, 2023)
Abstract The development of the film industry, especially Hollywood, which is currently a trendsetter, has introduced new prominent fictional characters. This is supported by technological advancements in graphics and computer visual effects. Animals are living creatures that are often used as references for the development of fictional characters, icons, and characterizations, not only in terms of physical appearance but also their characteristics. For example, this has brought about a new trend in the enhanced depiction of fable stories and also provides an opportunity to introduce unique wildlife from a particular region. It not only introduces local animals specific to an area but also enables the introduction of local culture. Indonesia itself has many regions that possess distinctive animals and cultural values with artistic significance. One example is the rhinoceros, which is an endemic animal of the western part of the island of Java (Banten), the buffalo from Sumatra (Padang), and the cockatoo from Sumatra (Lampung). At the end of this study, it will encompass the design of interesting characters inspired by the unique animals of Indonesia's regions, depicted as martial arts characters with distinct regional appearances. This aims to introduce not only the animal characters but also the culture of those regions. Keywords Wildlife; Endemic; Animal; Actions; Figures